2014
DOI: 10.1007/s00330-014-3358-8
|View full text |Cite
|
Sign up to set email alerts
|

Optic radiation damage in multiple sclerosis is associated with visual dysfunction and retinal thinning – an ultrahigh-field MR pilot study

Abstract: • Focal destruction of the optic radiation is detectable by 7 T MRI. • Focal optic radiation damage is common in MS. • Optic radiation damage is associated with RNFL thinning, detectable by OCT. • Optic radiation damage is associated with delayed VEP and visual dysfunction. • RNFL thickness in non-optic neuritis eyes correlates with optic radiation demyelination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
74
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 43 publications
5
74
0
4
Order By: Relevance
“…Similar associations were seen in a study looking at focal atrophy in the optic radiations and RNFL thinning in early MS [78]. Whilst initial studies observed this relationship in patients with or without a history of ON [47,77], more recent studies [60,78] found that this relationship was significant only in MS patients without previous ON. Additionally, another study found no correlation between DTI measures in the optic radiations and RNFL thickness in a cohort of RRMS patients with a history of ON [49].…”
Section: Optic Radiationsupporting
confidence: 75%
See 3 more Smart Citations
“…Similar associations were seen in a study looking at focal atrophy in the optic radiations and RNFL thinning in early MS [78]. Whilst initial studies observed this relationship in patients with or without a history of ON [47,77], more recent studies [60,78] found that this relationship was significant only in MS patients without previous ON. Additionally, another study found no correlation between DTI measures in the optic radiations and RNFL thickness in a cohort of RRMS patients with a history of ON [49].…”
Section: Optic Radiationsupporting
confidence: 75%
“…Peripapillary RNFL thickness and macular volume was associated with lesion volume, NAWM and abnormal DTI measurements in the optic radiations of MS patients [47,60,72,77]. Similar associations were seen in a study looking at focal atrophy in the optic radiations and RNFL thinning in early MS [78]. Whilst initial studies observed this relationship in patients with or without a history of ON [47,77], more recent studies [60,78] found that this relationship was significant only in MS patients without previous ON.…”
Section: Optic Radiationmentioning
confidence: 55%
See 2 more Smart Citations
“…Wallerian degeneration (anterograde axonal degeneration) and retrograde axonal degeneration (Bdying-back^degeneration) have been suggested to occur as mid-to long-term damage after acute inflammatory changes [22], e.g., due to ON or after lesional development within the OR. Beyond focal axonal damage and its direct mid-term consequences, the question has emerged as to whether trans-synaptic degeneration may play an additional significant role in chronic disease development and neurodegeneration [23].…”
Section: Ms Visual Pathway White Matter Damage Patternsmentioning
confidence: 99%